PREPARATION AND PROPERTIES OF MURINE ANTI-IDIOTYPIC MONOCLONAL ANTIBODIES RECOGNIZING PRIMARY RABBIT POLYCLONAL ANTIBODIES AGAINST MORPHINE DERIVATIVES - A. V. Trofimov; A. M. Ischenko; A. Ya. Rak; V. E. Sergeeva; A. S. Simbirtsev; N. B. Gamaleya; A. G. Berzina; N. V. Stankova; L. I. Ulyanova; T. A. Klimova (Медицинская иммунология, 2019)
Anti-idiotypic antibodies (Ab2), according to the network theory of Jerne, are second-generation immunoglobulins that are produced against the idiotype of an antibody to a specific antigen. Despite the large number of works devoted to the study of the properties of these proteins, their role in the regulation of the immune system is not fully known. It may consist in maintaining or blocking a minimal immune response to the antigen. The study of Ab2 is of great practical and scientific importance. The special properties of Ab2, namely, the ability to partially reproduce the structure of the primary antigen and, upon immunization, induce the appearance of tertiary antibodies, which, like first-generation antibodies, can bind to the antigen, have found application in the development of Ab2-based vaccines, in particular, for the treatment of tumors. In view of the presence of a number of limitations on research related to psychoactive substances, the development of Ab2- based vaccines against drug addiction also seems promising. To example, anti-idiotypic antibodies obtained for this purpose possessing a cocaine-like structure are described in the literature. In this work, murine monoclonal anti-idiotypic antibodies (mAb2) mimicking the structure of various morphine derivatives were obtained. Rabbit polyclonal antibodies to the 6-hemisuccinyl derivative of morphine conjugated with bovine serum albumin isolated by affinity chromatography were used as primary antibodies for immunization. Four hybridoma clones were obtained as a result of the fusion of immunized mice lymphocytes with mouse Sp2/0 mouse myeloma cells by the Milstein-Köhler method. After growth in animals, mAb2 produced by hybridoma cells were affinity purified. We investigated the physicochemical and antigenic properties of the isolated antibodies. It was shown that the obtained mAb2 differ in immunological specificity, competing in different degree with morphine derivatives for binding to first-generation antibodies. We tested the possibility of using the obtained mAb2 as antigen analogues in the solid-phase enzyme-linked immunosorbent assay to determine the titer of primary antibodies against morphine in the blood serum of laboratory animals immunized with morphine derivatives. Based on the obtained anti-idiotypic antibodies, it is proposed to develop test systems to determine the serum opiate-specific antibodies in people after specific vaccination for therapeutic or prophylactic purposes to avoid the use of drugs as antigens immobilized on the solid phase in the analysis.